2009
DOI: 10.1017/s0950268808001908
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Q fever outbreak in a rural area of The Netherlands

Abstract: A Q fever outbreak occurred in the southeast of The Netherlands in spring and summer 2007. Risk factors for the acquisition of a recent Coxiella burnetii infection were studied. In total, 696 inhabitants in the cluster area were invited to complete a questionnaire and provide a blood sample for serological testing of IgG and IgM phases I and II antibodies against C. burnetii, in order to recruit seronegative controls for a case-control study. Questionnaires were also sent to 35 previously identified clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 22 publications
7
125
0
4
Order By: Relevance
“…Airborne transmission of contaminated dust particles could have been facilitated by the unusually hot and dry weather in the spring of 2007. In 2007, the outbreak was concentrated around a single village and in this village a case-control study was performed [29]. Contact with manure, hay, and straw proved to be a risk factor.…”
Section: Public Health and The Environment (Rivm)mentioning
confidence: 99%
“…Airborne transmission of contaminated dust particles could have been facilitated by the unusually hot and dry weather in the spring of 2007. In 2007, the outbreak was concentrated around a single village and in this village a case-control study was performed [29]. Contact with manure, hay, and straw proved to be a risk factor.…”
Section: Public Health and The Environment (Rivm)mentioning
confidence: 99%
“…Critically, subject to a suitable extraction method, real-time PCR might be used to detect the presence of C. burnetii within a multitude of different sample types, including bedding material, straw, and birth products (including placental and fetal material), that could be associated with the production of contaminated aerosols, which may be potentially involved in a disease outbreak. 9,17,23 Polymerase chain reaction assays may also be used to detect C. burnetii in milk. 15 The current study has shown that suitable detection methods are available in many laboratories to detect C. burnetii in a disease outbreak.…”
mentioning
confidence: 99%
“…[7][8][9]20 Abnormally dry and drought conditions in the region of Missouri where Community A is located during Summer 2013 could have been especially conducive to windborne spread of C. burnetii in dust. 10,[21][22][23][24] Additionally, uncovered compost piles and transport of uncovered manure or bedding were reported or observed in Community A. These practices can result in aerosolization of C. burnetii, particularly on windy days, putting environmental workers and the larger community at risk.…”
Section: Discussionmentioning
confidence: 99%